Bier block as a successful management of a patient with intractable complex regional pain syndrome (CRPS) type 1: A case report. Issue 7 (21st July 2021) - Emami, Seyed Ali; Majedi, Hossein; Espahbodi, Ebrahim; Sanatkar, Mehdi
Abstract: Bier block was successful in the pain management of complex regional pain syndrome (CRPS) type 1. Abstract : Bier block was successful in the pain management of complex regional pain syndrome (CRPS) type 1.